Gross rearrangement of Fe(II) aggregate structure by replacement of two H+ by two Li+: Visualizing altered structure of acid versus conjugate base. (1st December 2019) - Cook, Brian J.; Chen, Chun-Hsing; Pink, Maren; Caulton, Kenneth G.
Graphical abstract: The structural changes upon deprotonation of a penta-iron, tetraligand bis-hydroxide species is reported. Prior to deprotonation, the species is an open, elongated C2 -symmetric species. Upon treatment with base, the species contracts to a more compact species with a highly hydrophilic core and hydrophobic shell. Abstract: Double deprotonation of [(H2 L)FeCl2 ]2 ·FeCl2 with LiN(SiMe3 )2 under varying conditions occurs to give the acid [(THF)2 LiClFe2 L2 ]2 [Fe(OH)2 ], 1, and the lithium salt of its doubly deprotonated conjugate base Li2 ([(THF)1.5 LiClFe2 L2 ]2 [Fe(O)2 ]), 2 . Single crystal X-ray determination of both structures shows that replacement of two protons by two Li + causes both oxo and chloride ligands to adopt higher connectivity bridging roles. This illustrates the core event of moving towards more closed and higher dimensionality. The added lithium ions bind to various nucleophilic centers in the resulting intimate ion pair, all with general contraction of the metal framework, as an illustration of the general shrinkage towards a compact solid as hydroxide is converted to oxide.